Exogenous melatonin alleviates drought stress in cotton by enhancing root cortical activity and metabolic adaptation - Zhang, Haitao; Guo, Congcong; Sun, Hongchun; Zhu, Lingxiao; Zhang, Ke; Zhang, Yongjiang; Wang, Zhanbiao; Li, Cundong; Liu, Liantao (Frontiers in Plant Science, 2025)
IntroductionThe root cortex plays a critical role in water uptake and metabolic activity, directly influencing root functionality. However, despite melatonin’s known role in plant stress tolerance, its mechanisms in modulating root cortical anatomy and metabolic adaptation under drought remain unclear. This study examines the impact of exogenous melatonin on the root cortex of cotton under drought stress, focusing on its relationship with water uptake and drought resilience.MethodsCotton plants (cv. Lumian 532) were subjected to drought stress (8% PEG 6000) with foliar application of melatonin (100 μmol/L) to evaluate its effects on root cortical integrity and water uptake.ResultsThe results demonstrated that melatonin application significantly increased living cortical area (LCA) and cortical thickness of roots under drought stress, and the effect was more obvious near the middle segment of the root (13 cm from the root tip). Melatonin also enhanced osmotic regulation, increased respiratory enzyme activity, and improved specific root length uptake rates for water and key nutrients. Furthermore, melatonin promoted root and above-ground growth, as evidenced by increases in root length, plant height, stem diameter, and leaf area. Notably, LCA positively correlated with osmotic substance accumulation, root respiration, and absorption capacity under drought conditions.DiscussionIn conclusion, exogenous melatonin synergistically enhances drought resistance by maintaining cortical integrity, improving water absorption efficiency, and activating respiratory metabolism, thereby enhancing cotton growth and drought resistance. These findings underscore melatonin as a promising regulator for enhancing drought resistance.